2018
DOI: 10.3389/fphys.2018.01014
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Results on the Association Between TP53 Codon 72 Polymorphism With the Susceptibility to Oral Cancer

Abstract: Objectives: TP53 is an important tumor suppressor gene to maintain genomic integrity, and its mutations increase the susceptibility to oral carcinoma. Previous published studies have reported the relation of TP53 codon 72 polymorphism with the risk of oral carcinoma, but the results remain controversial and inconclusive.Methods: We therefore utilized meta-analysis based on a comprehensive search in PubMed, EMBASE, and Google of Scholar databases up to August 19, 2017.Results: Total 3,525 cases and 3,712 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
(80 reference statements)
1
5
0
Order By: Relevance
“…In an updated meta-analysis, Sun et al [ 12 ] conducted an updated meta-analysis of 17 case–control studies from 16 articles with 3047 cases of OSCC and 3305 health controls, and concluded that there was no significant association between TP53 codon 72 polymorphism and the risk of OSCC in either the Asian or Caucasian population. This data was in agreement with the result from another contemporaneous meta-analysis [ 28 ]. Interestingly, Sun et al [ 12 ] performed an additional meta-analysis of 6 case–control studies from 5 articles with 391 cases of OLK and 763 health controls, and also found that no significant association of TP53 codon 72 polymorphism with OLK susceptibility.…”
Section: Discussionsupporting
confidence: 93%
“…In an updated meta-analysis, Sun et al [ 12 ] conducted an updated meta-analysis of 17 case–control studies from 16 articles with 3047 cases of OSCC and 3305 health controls, and concluded that there was no significant association between TP53 codon 72 polymorphism and the risk of OSCC in either the Asian or Caucasian population. This data was in agreement with the result from another contemporaneous meta-analysis [ 28 ]. Interestingly, Sun et al [ 12 ] performed an additional meta-analysis of 6 case–control studies from 5 articles with 391 cases of OLK and 763 health controls, and also found that no significant association of TP53 codon 72 polymorphism with OLK susceptibility.…”
Section: Discussionsupporting
confidence: 93%
“…After duplicate elimination, 3924 records were considered potentially eligible and screened according to titles and abstracts, leaving a sample of 92 studies for full text evaluation. Finally, 85 studies meeting all eligibility criteria were included for critical analysis and evidence synthesis in our scoping review [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…To date, a significant number of systematic reviews and meta-analyses have been published on different implications of the TP53 gene and its product in carcinogenesis of the head and neck, particularly the oral cavity. Five meta-analyses have investigated the association between the rs1042522 polymorphism and susceptibility to the development of oral cancer [ 60 , 61 , 77 , 83 , 95 ]. The oncogenic mechanism linked to this polymorphism is due to the substitution of proline for arginine at codon 72, located in exon 4 of the TP53 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation in the TP53 gene is the most common alteration found in the carcinogenesis of HNSCC in humans. In human medicine, many studies relate the expression of this protein (assessed by IHC) and exposure to risk factors such as tobacco consumption [ 52 , 53 ]. Out of the studies investigating the exposure to ETS in cats with oral SCC, only two analyzed the expression of p53 in oral tissue and its association with exposure to ETS [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%